A TERRITORIALIZAÇÃO DA POLÍTICA DE ASSISTÊNCIA SOCIAL DE TRÊS LAGOAS/MS: UMA ANÁLISE A PARTIR DA GESTÃO LOCAL - Ferreira, Lidiane Antonia (2023)
The main objective of this article is to apprehend the territorialization of the Social Assistance Policy in the city of Três Lagoas / MS. To this end, it was essential the bibliographic survey of the theme and the documentary classification that is based on laws, regulations and resolutions. A posteriori, the data from the Federal Government's Single Registry was collected and analyzed qualitatively, through the Social Assistance Surveillance Sector of the Municipal Social Assistance Secretariat of the city of Três Lagoas / MS, which supported the coding, mapping and cartographic illustration of the beneficiary public of the Bolsa Família Program is territorialized. It is noteworthy that the debate on Geography and its concept of Territory within the scope of Public Policy on Social Assistance, initiated in the 2000s, gives the meaning of the debate to public policy on screen. Therefore, the concept and the understanding of the territory, in addition to the location of people, groups and social phenomena, in a predetermined area, helps to apprehend the space of production and reproduction of concrete social relations that gains visibility from the inequalities in it gifts. The assimilation of the importance of the agents' social role, the recognition of the territories in which the Social Assistance Reference Centers (CRAS) operate, which are characterized as the gateway to the Social Assistance Policy; the importance of conceiving and understanding the territory and its respective networks and representations can and should be interpreted in multiple dimensions that make it possible to enhance the planning, monitoring and evaluation actions of the Social Assistance Policy.